Relationship of Husband Support, Culture, and Sexual Comfort with Mother's Interest in Using IUD at Tanah Alas District Public Health Southeast Aceh - Siska Suci Triana Ginting; Lidya Natalia Sinuhaji; Juliana Munthe; Oktaria Kristin; Cyndi Pane (Institute of Computer Science (IOCS), 2022)
High population growth causes a population explosion resulting in higher unemployment, crime, and worsening of other social conditions, quality of life, poverty levels, and increased life expectancy. Globally, the world's population reached 7.6 billion people in 2019 with a growth of more than 80 million people per year. Factors causing the high rate of population growth include improving economic growth, mobilization, migration, technology, development, knowledge, use of contraceptives, and others (WHO, 2019). Indonesia still ranks fourth with the most population in the world after China, India, and America. The distribution of Indonesia's population in 2021 has reached270 203 917 people, consisting of 136 661 899 males and 133 542 018 females. Aceh province numbered 5 274 871 inhabitants. The trend of population growth is due to rapid economic growth and the region has become a destination for growth centers (growth poles) which further increases the immigrant population (Central Bureau of Statistics, 2020).